Mutant Prevention Concentration of Ciprofloxacin against Klebsiella pneumoniae Clinical Isolates: An Ideal Prognosticator in Treating Multidrug-Resistant Strains - B. Aditi Priyadarshini; Krishnan Mahalakshmi; Venkatesan Naveen Kumar (International Journal of Microbiology)
Background. Fluoroquinolone-resistant Klebsiella pneumoniae poses a therapeutic challenge when implicated in urinary tract infections, pyelonephritis, pneumonia, skin infections, osteomyelitis, and respiratory infections. The mutant prevention concentration (MPC) represents a concentration threshold above which increase of resistant mutants occurs rarely. The aim of the present study is to determine the MPC among ciprofloxacin-resistant K. pneumoniae clinical isolates. Materials and Methods. A total of 240 clinical isolates of K. pneumoniae were collected from a tertiary care hospital. The MPCs were determined for 24 selected strains using an inoculum of 1010 CFU/ml in Müller–Hinton agar plates with serial/various concentrations (0.003–100 μg) of ciprofloxacin. In addition to the MPC, phenotypic screening for ESBL, AmpC, and carbapenemase was performed. The detection of qnr genes for 24 isolates and DNA sequencing for six isolates were performed. Results. Ciprofloxacin resistance was observed in 19.6% of the K. pneumoniae clinical isolates. Among the ciprofloxacin-resistant isolates, 14 isolates showed an MPC value of more than 100 μg. The MPC ranged between 100 μg and 20 μg for ciprofloxacin-resistant isolates. ESBL producers and qnr gene-producing strains had a high MPC. 11 isolates showed the presence of either qnrB or qnrS genes. None of the samples showed the presence of the qnrA gene. Conclusion. From our study, we infer that ESBL producers and qnr gene-possessing strains are frequently resistant to ciprofloxacin. Estimation of the MPC in the case of multidrug-resistant isolates in the clinical setup may help in treating these drug-resistant strains.